Estudo clínico randomizado de diferentes protocolos de clareamento dentário com peróxido de hidrogênio a 7,5% - Carneiro, Jéssica Rodrigues Mendes (2016)
Bleaching is a conservative technique and it much sought after by patients looking for an improvement in smile esthetics. The objective of this study was to evaluate the effectiveness of bleaching treatment, with 7.5% hydrogen peroxide at different time intervals, and evaluate the intensity of related tooth sensitivity. For this, 60 patients were selected and divided into three groups: group PH10 - used the gel for 10 min a day; group PH30 – 30 min; group PH60 – 60 min. The volunteers had the autonomy to stop bleaching when they were satisfied with the result, ranging between 14 and 42 days. Two sensitivity tables (Visual analogue scale and 5-point verbal rating scale) were given to the participants to be filled in daily on the levels of sensitivity. Color assessments were made using the Vitapan Classical Scale and Easyshade spectrophotometer at 14, 21, 28 and 42 days of treatment and 1 month after the end of the bleaching, to evaluate color rebound effect. Degree of patient satisfaction was measured by a questionnaire. For data analysis, Fisher’s exact test compared the percentage of satisfied with unsatisfied participants in each of the three groups (α=0.05). The mean number (± standard deviation [SD]) of days required to achieve the participant satisfaction in each of the three groups was calculated and statistically analyzed using the ANOVA and t-test (α=0.05). Intensity of sensitivity was evaluated using the Kruskal-Wallis test (α=0.05). To analyze the difference of color of both methods (spectrophotometer and color scale) two tests were used: for the same period in different groups the Kruskal-Wallis test was performed (α=0.05), and for the same group at different time intervals the Friedman test was used (α=0.05). The three methods were effective, with group PH10 being less effective than group PH60 with only the color scale evaluation method in the analysis of tooth 13. One month after the end of the treatment, there was no significant difference with the results found immediately after the treatment period. Group PH10 had a higher mean number of days of gel use, a lesser degree of satisfaction with the end result, and less pain when compared to the others. It can be concluded that the decrease in the daily time-use of 7.5 % hydrogen peroxide had no effect on its effectiveness, and it brought benefit to patients, as well as making the treatment faster, it decreased the discomfort of sensitivity.